2014
DOI: 10.1136/heartjnl-2014-306916.3
|View full text |Cite
|
Sign up to set email alerts
|

Nadph Oxidase Activation and Oxidative Stress in High-Fat Diet-Induced Hypertension and Metabolic Disorders

Abstract: Dietary obesity is a major risk factor for the development of cardiovascular diseases. However, the mechanism of high fat diet (HFD)-induced vascular dysfunction remains unclear. In this study we investigated the role of a Nox2-containing NADPH oxidase in high fat diet (HFD: 45% kcal fat)-induced metabolic disorders using Nox2/ApoE double knockout mice in comparison to age-matched ApoE−/− mice on the C57BL/6 background (n=9). ApoE−/− mice under 10 weeks of HFD had significant increases in body weight (NCD 27.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Nox2-derived ROS production caused by excessive glucose and insulin challenge also elicits ERK1/2 activation, resulting in endothelial cell injury, dysfunction and death [30]. Studies report that Nox2 augments endothelial p-ERK1/2 expression after chronic HFD feeding [7,11]. Our findings strongly suggest a contribution of myocardial Nox2 in HFD-induced ERK1/2 activation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Nox2-derived ROS production caused by excessive glucose and insulin challenge also elicits ERK1/2 activation, resulting in endothelial cell injury, dysfunction and death [30]. Studies report that Nox2 augments endothelial p-ERK1/2 expression after chronic HFD feeding [7,11]. Our findings strongly suggest a contribution of myocardial Nox2 in HFD-induced ERK1/2 activation.…”
Section: Discussionsupporting
confidence: 60%
“…HFD feeding reduces insulin sensitivity as early as five days of intervention [9], associates with oxidative stress and promotes vascular damage involving cardiac remodelling, hypertrophy and apoptosis [10]. Aortic Nox2 overexpression occurs in HFD-fed ApoE knockout mice in unison with increased activation of both Akt and ERK1/2 and is associated with endothelial dysfunction [11]. Moreover, it has been reported that caloric restriction reverses endothelial oxidative damage in these conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Findings reveal that individuals with hyperlipidaemia produce more reactive oxygen species (ROS) 10 . This could be due to a fat-rich diet increasing the expression of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase genes 11 , which is the primary enzyme responsible for ROS synthesis 12 resulting in increased ROS formation in cells 13 . Low-density lipoprotein (LDL) oxidation is triggered by the presence of ROS, which activates inflammatory cytokines, mediators and chemokines produced by invading resident macrophages.…”
mentioning
confidence: 99%